Aircraft hijacking and the developing law - Ghosh, S.K. (New Delhi, 1985)
More than five decades have passed since the first recorded successful aircraft seizures. With the increase in the number of Aircraft Hijackings, the international community recog nised the existence of a threat to global air safety, organised and executed several Conventions, Agree ments and Resolutions, discussed in this work.
Keywords: Larceny